The dynamics behaviors of Chay neuron model under different parameters. (25th October 2018) - Kaijun, Wu; Chao, Yu; Dicong, Wang
Summary: Based on C‐language and Matlab, this paper numerically simulates the dynamic behaviors of Chay neuron model under different parameters using the bifurcation diagram of Inter‐spike interval (ISI), time response graph, and phase diagram. The results show that the period‐adding, period‐doubling, and chaos phenomena of Chay neuron model were observed intuitively in the bifurcation diagram of ISI controlled by different parameters, and these phenomena were also found in the corresponding time response graph and phase diagram. These results provide a basis for further understanding the physiological characteristics of Chay neuron model.